2018
DOI: 10.1371/journal.pone.0197544
|View full text |Cite
|
Sign up to set email alerts
|

Successful direct acting antiviral (DAA) treatment of HCV/HIV-coinfected patients before and after liver transplantation

Abstract: ObjectivesThe aim of this multicenter retrospective study was to investigate safety and efficacy of direct acting antiviral (DAA) treatment in the rare subgroup of patients with HCV/HIV-coinfection and advanced liver cirrhosis on the liver transplant waiting list or after liver transplantation, respectively.MethodsWhen contacting 54 German liver centers (including all 23 German liver transplant centers), 12 HCV/HIV-coinfected patients on antiretroviral combination therapy were reported having received addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…Between alcohol abuse and antiretroviral therapy‐related toxicity, hepatitis C virus (HCV) co‐infection has been so far the major underlying cause, with a reported prevalence of 70%. 1 , 2 , 3 Liver transplantation (LT) has been demonstrated to be a feasible and effective treatment for ESLD HIV‐positive patients, even in the presence of hepatocellular carcinoma (HCC) diagnosis, reaching outcomes comparable to non‐HIV patients. 1 , 2 , 3 Nonetheless, HCV/HIV co‐infected LT recipients have been characterized by a dismal outcome, mainly due to a severe HCV recurrence on the liver allograft, that is accelerated by HIV co‐infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between alcohol abuse and antiretroviral therapy‐related toxicity, hepatitis C virus (HCV) co‐infection has been so far the major underlying cause, with a reported prevalence of 70%. 1 , 2 , 3 Liver transplantation (LT) has been demonstrated to be a feasible and effective treatment for ESLD HIV‐positive patients, even in the presence of hepatocellular carcinoma (HCC) diagnosis, reaching outcomes comparable to non‐HIV patients. 1 , 2 , 3 Nonetheless, HCV/HIV co‐infected LT recipients have been characterized by a dismal outcome, mainly due to a severe HCV recurrence on the liver allograft, that is accelerated by HIV co‐infection.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 Liver transplantation (LT) has been demonstrated to be a feasible and effective treatment for ESLD HIV‐positive patients, even in the presence of hepatocellular carcinoma (HCC) diagnosis, reaching outcomes comparable to non‐HIV patients. 1 , 2 , 3 Nonetheless, HCV/HIV co‐infected LT recipients have been characterized by a dismal outcome, mainly due to a severe HCV recurrence on the liver allograft, that is accelerated by HIV co‐infection. 4 Nowadays, direct‐acting anti‐HCV drugs (DAAs) have been effectively controlling such risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although higher rates of acute graft rejection in PLWH undergoing SOT are still a matter of concern (in part consequent to difficulties in adapting immunosuppressors concomitantly with certain ARTs), several studies have reported patient and graft survival rates in long-term follow-up of HIV-positive kidney-transplant recipients similar to those who were HIV negative [25][26][27]. Regarding liver transplantation in HIV/HCV co-infected patients, since DAAs became available, SVRs prior to and post liver transplantation are comparable to those of HCV-mono-infected patients [28,29]. Thereby, graft and patient survival has shown improvement over time and outcomes of co-infected liver recipients are expected to match those of HCV-mono-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a liver transplant is not a viable option for most PWH in need, and many with advanced liver disease fail to link to HCV sub-specialty care. 7 Challenges to this conventional approach include the need for a sub-specialty referral and insurance approval in non-universal healthcare systems and long waiting times for a hepatology intake appointment. 8 The combination of PWH with ongoing barriers to care, internalized stigma, and low HCV knowledge also accentuate the lack of HCV linkage to care of some PWH with advanced liver disease to hepatology services.…”
Section: Discussionmentioning
confidence: 99%